Study of Organoleptic Nutmeg Fruit Dodol Quality - Mustamin A. Masuku; Misran Lawani; Erna Umasugi (Sangia Publishing, 2020)
Dodol is a semi-wet food that has a plastic texture. The typical organoleptic properties of dodol are brown and have a sweet, savory and legit taste with a plastic texture. Nutmeg meat has the potential to be processed into various food products such as candied nutmeg, nutmeg syrup, jam, nutmeg juice, instant nutmeg drink, nutmeg jelly, nutmeg wine, vinegar acid, gelatin hard candy and dodol. Processing nutmeg meat into nutmeg dodol can add value to nutmeg products and increase farmers' income. The purpose of this study was to produce nutmeg dodol with the best organoleptic properties. Dodol from nutmeg meat and banana flour mulu bebe produces a colour value of 3.64-3.70 (dislike), flavour 3.25-3.59 (rather dislike), and aroma of 3.75-4.15 (dislike). The ratio of the addition of nutmeg meat 65% and banana flour mulu bebe 35% meets the quality of SNI dodol, the ratio of addition of nutmeg meat 45% and banana flour mulu bebe 55% produces nutmeg dodol favoured by consumers.